SISTEM BAGI HASIL DALAM AKAD MUDHARABAH PADA PERJANJIAN KERJASAMA PEMBUATAN BATU BATA DI ALASBULUH WONGSOREJO BANYUWANGI - Imam Fawaid; Abd. Rahman Saleh; Misba Huddin; Sri Windari (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2025)
One form of cooperation that is often used in the context of Islamic economics is the mudharabah agreement. One party acts as the capital owner, and the other party as the business manager. Brick making is a business sector that has great potential, especially in rural areas. Therefore, the problem arises of how to implement the profit sharing system in the mudharabah agreement in the brick making agreement in Alasbuluh Wongsorejo Banyuwangi? The type of research used is field research, that is, researchers go directly into the field to conduct research so they can see and understand the objects to be discussed. The results of this research indicate that the profit sharing system in the mudharabah agreement in the brick making agreement in Alasbuluh Wongsorejo is an application of cooperation between capital owners and managers. The capital provided is in the form of a loan with an agreement at the beginning of the contract. And the profit sharing system in the mudharabah agreement in the brick-making cooperation agreement in Alasbuluh Wongsorejo Banyuwangi in its implementation is not fully in accordance with Islamic law, one of the things that is appropriate is the terms of a consensual agreement. Cooperation agreement activities carried out by the community in Alasbuluh Wongsorejo Banyuwangi, in its implementation there is a clear concept of cooperation and is justified by sharia as long as the business activity does not conflict with the values ​​of Islamic sharia